2021
DOI: 10.1002/hpja.551
|View full text |Cite
|
Sign up to set email alerts
|

On‐campus food purchasing behaviours and satisfaction of Australian university students

Abstract: Issue addressed: Many university students have unhealthy dietary intake. The food environment on university campuses is a potentially important contributor to students' diet. This study aimed to describe on-campus food purchasing behaviours; satisfaction with the cost and availability of foods and beverages on-campus; and preferences for the on-campus food environment, in a sample of Australian university students.Methods: An online cross-sectional survey of 409 students at the University of Newcastle, Austral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Food environment and purchasing on campus may affect the diet quality of tertiary education students, although this was not measured in our study. Previous studies from the U.S. and Australia found more frequent purchases of foods and beverages on campus were associated with poorer diet quality and less healthy eating habits, such as less frequent breakfast and higher consumption of energy-dense, nutrient-poor choices [ 56 , 57 , 58 ]. Higher availability of healthy options with cheaper prices were often suggested by food environment audits on campus and student surveys [ 38 , 56 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Food environment and purchasing on campus may affect the diet quality of tertiary education students, although this was not measured in our study. Previous studies from the U.S. and Australia found more frequent purchases of foods and beverages on campus were associated with poorer diet quality and less healthy eating habits, such as less frequent breakfast and higher consumption of energy-dense, nutrient-poor choices [ 56 , 57 , 58 ]. Higher availability of healthy options with cheaper prices were often suggested by food environment audits on campus and student surveys [ 38 , 56 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…University students with FI report that one of the barriers to accessing food more frequently (very often/often) compared to food-secure students is the high cost of food [ 10 ]. For instance, in a sample of Australian university students, the majority were dissatisfied with the cost of food and drinks and one of the main changes suggested in the campus food environment was cheaper food [ 43 ]. The cost of the diet increases as the quality of the diet increases.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, regarding the food environment in universities, one study showed that most college students were dissatisfied with the types of main meals and snacks available on campus. The main changes these students suggested included healthier options and higher-quality foods [ 43 ]. Another study that evaluated the characteristics of the food sales establishments located inside and outside of university centers in Mexico identified that none offered the nutritional value of the dishes, only 20.3% of the establishments evaluated had a salad bar, 46.2% provided preparations with vegetables, and 51.9% offered sugar-free drinks.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been a growing interest in examining food choices and dietary habits among college students as well as the healthfulness of the university food environment [ 28 ]. Much of the research examines predictors of healthy food purchasing [ 13 , 18 , 19 , 29 , 30 , 31 , 32 , 33 , 34 ] and perceptions of the campus environment [ 19 , 35 , 36 , 37 , 38 ]. Additionally, some research has investigated the quality of food and beverages available to college students [ 5 , 16 , 17 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%